Support for economic activity of people aged 50+ in Poland: The best solutions of the government's programme solidarity of generations - Bogusława Urbaniak; Justyna Wiktorowicz (Comparative Economic Research. Central and Eastern Europe, 2014)
The article aims to assess some selected solutions of the Polish government's programme "Solidarity of generations" [SG] designed to support economic activity among people aged 50+. It presents the results of a national survey conducted in the first half of 2012, mainly the outcomes of questionnaire interviews carried out with representative samples of people aged 45+ and employers. Studies under the name "Diagnosis of the current situation of females and males 50+ on the labour market in Poland [D50+]" were conducted within the project "Equal Opportunities in the Labour Market for People Aged 50+". In addition to standard methods of descriptive analysis and the assessment of relations, factor analysis is also used to identify the main types of activities advancing opportunities for people aged 45+. Some solutions of the government's programme, such as the protection of employees from dismissal during the last four years before their retirement, were sometimes evaluated very differently by employers and people aged 45+. At the same time, both employers and people aged 45+ were favourable about free training and public subsidies to set up jobs for an unemployed persons aged 50+. According to the factor analysis results, the most important activities for people aged 45+ to have equal opportunities in the labour market are those activities that directly improve their qualifications. Although this finding is endorsed by both employers and people aged 45+, the insufficient systemic support for life-long learning limits the number of opportunities they could use to increase their employment activity. The variety of evaluations presented by the beneficiaries of the government programme should be taken into account in planning its modification.
Keywords: 330; ageing of population; economic activity; older workers; state intervention for employment of people aged 50+; lifelong learning